2018
DOI: 10.1021/acs.jpcc.8b05030
|View full text |Cite
|
Sign up to set email alerts
|

New Calcium Hydrides with Mixed Atomic and Molecular Hydrogen

Abstract: Two new polyhydrides of calcium have been synthesized at high pressures and high temperatures and characterized by Raman spectroscopy, infrared spectroscopy, and synchrotron X-ray diffraction. Above 20 GPa and 700 K, we synthesize a phase having a monoclinic (C2/m) structure with Ca 2 H 5 composition, which is characterized by a distinctive vibration at 3789 cm −1 at 25 GPa. The observed Raman spectrum is in close agreement with first-principles calculations of a Ca 2 H 5 structure characterized by a lattice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 73 publications
4
52
0
Order By: Relevance
“…S13) weakens the H-H bond in these ternaries, in-line with the findings for CaH 4 . 42 The Bader charges illustrate that S becomes negatively charged because of electron transfer from Ca, and accordingly the interaction between these two atoms, as gauged by the -ICOHPs, is non-negligible, and even larger than in CaS at comparable pressures. The H-S bond strength is of a similar magnitude as the Ca-S interaction, and the markedly smaller H-Ca interaction is on par with results obtained previously for CaH 4 .…”
Section: N H 2 / ( N H 2 + N C a S )mentioning
confidence: 99%
“…S13) weakens the H-H bond in these ternaries, in-line with the findings for CaH 4 . 42 The Bader charges illustrate that S becomes negatively charged because of electron transfer from Ca, and accordingly the interaction between these two atoms, as gauged by the -ICOHPs, is non-negligible, and even larger than in CaS at comparable pressures. The H-S bond strength is of a similar magnitude as the Ca-S interaction, and the markedly smaller H-Ca interaction is on par with results obtained previously for CaH 4 .…”
Section: N H 2 / ( N H 2 + N C a S )mentioning
confidence: 99%
“…The first successful synthesis of a material assuming this structure type was CaH 4 . [32] Shortly thereafter another group synthesized this same phase, [46] and I4=mmm symmetry CeH 4 , [47] ThH 4 , [48] YH 4 [49] and NdH 4 [41] compounds were made suggesting that other isotypic high-pressure hydrides may soon be discovered. A number of these phases are predicted to either be semiconductors or poor metals within their stability range (e. g. CaH 4 , [32] SrH 4 [34] ), to have relatively low T c values (e. g. LaH 4 , [19] ZrH 4 , [30] ThH 4 [44] and NdH 4 [41] ), or their superconducting properties have not yet been calculated (e. g. CeH 4 , PrH 4 , PmH 4 , SmH 4 , EuH 4 , GdH 4 , DyH 4 , HoH 4 , ErH 4 , TmH 4 , YbH 4 and LuH 4 [18] ).…”
Section: Introductionmentioning
confidence: 96%
“…[32] Shortly thereafter another group synthesized this same phase, [46] and I4=mmm symmetry CeH 4 , [47] ThH 4 , [48] YH 4 [49] and NdH 4 [41] compounds were made suggesting that other isotypic high-pressure hydrides may soon be discovered. A number of these phases are predicted to either be semiconductors or poor metals within their stability range (e. g. CaH 4 , [32] SrH 4 [34] ), to have relatively low T c values (e. g. LaH 4 , [19] ZrH 4 , [30] ThH 4 [44] and NdH 4 [41] ), or their superconducting properties have not yet been calculated (e. g. CeH 4 , PrH 4 , PmH 4 , SmH 4 , EuH 4 , GdH 4 , DyH 4 , HoH 4 , ErH 4 , TmH 4 , YbH 4 and LuH 4 [18] ). Only MgH 4 (81 K at 255 GPa), [30] ScH 4 (92 K at 120 GPa, [38] 67-81 K at 195 GPa, [36] and 98 K at 200 GPa [37] ), and YH 4 (84-95 K at 120 GPa [50] ) are predicted to have T c values higher than the boiling point of liquid nitrogen, whereas the T c of ZrH 4 (47 K at 230 GPa [30] ) and TbH 4 (41 K at 200 GPa [43] ) is predicted to be somewhat lower.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The inclusion of the ZPE corrections did not affect the identity of the thermodynamically stable stoichiometries at 100 and 150 GPa, but it added Na 2 S 2 and Na 2 S 3 to the 200 GPa hull, and pushed Na 2 S 4 away from it. Because phonon calculations (see the Supplementary Materials) confirmed that all of these phases were dynamically stable, and high-pressure experiments can lead to the formation of metastable species [86]; the structures of all of these phases are discussed below.…”
Section: Na-s System At High Pressurementioning
confidence: 99%